Teaching History from the inclusive educational practice perspective: analysis of Brazilian academic productions (2004-2021) (Olhar de Professor, 2023)
This article aims to understand and analyze the articulations between the teaching of History and the pedagogical practices aimed at Inclusive Education. To this end, we investigated a set of dissertations and theses – from 2004 to 2021 – that analyzed experiences of students, teachers, and other members of the school community regarding the didactic formulation and procedural execution of proposals for teaching History that raised the critical debate about inclusion in the classroom. This is a quantitative and qualitative study that surveyed the Digital Bank of Theses and Dissertations, based on categories of analysis, such as methodological approaches, concepts, connection with research lines, participating subjects and development locus of Brazilian academic productions. In the light of historiographical discussions related to the theme, we observed a significant increase in dissertations related to the use of ethnographic methodology for teachers’ reflection on the peculiar teaching-learning processes, mainly of students who have Pervasive Developmental Disorders.
Keywords: History Teaching. Inclusive education. Academic productions.